Examining the role of job resources on work engagement among academicians in a public university / Noorazima Asyikin Mohd Asri - Mohd Asri, Noorazima Asyikin (Faculty of Business and Management, 2020)
Rapidly changing business environment requires organization to gain competitive advantage in order to survive. As people is known to be the most valuable assets to an organization, having employees that are actively engaged in their work can positively leads to higher performance and subsequently contribute to the success of the organization. One of the predictors that would lead to work engagement among employees is through the dimensions of job resources which came from Job Demand-Resources Theory. Therefore, the main purpose of conducting this research is to examining the role of job resources on work engagement as well as to identify the most influential factor in job resources among academicians in UiTM Kampus Bandaraya, Melaka. Census study has been used to obtain the sample and questionnaire is the tool used by researcher to collect the data for this research. The data from 87% out of 101 academicians are collected then evaluated by using Statistical Package for the Social Science (SPSS) Version 23 Software. The result from Multiple Regression analysis indicates that only two dimensions in job resources which are autonomy and social support have positive significant relationship with work engagement while performance feedback is not significant. Moreover, Regression analysis revealed that, social support found to be the most influential variables towards work engagement among academicians in UiTM Cawangan Melaka Kampus Bandaraya.